La difícil adecuación entre el concepto político de ciudadano y la sociedad poscolonial chilena y rioplatense (1808-1818) - Enrique Fernández Domingo (Les Cahiers ALHIM)
The revolutionary political speech is analyzed with respect to the legal definition of the citizen who is presented as the fundamental basis of the sovereignty of the new states born as a result of the period of the independence wars taking place in Chile and rioplatense spaces.The study of constitutional texts shows ethnic and social conflicts of the colonial legacy and its reflection in political citizenship.